Search for the Soul of Black Preaching - Latimore, David G. (Theology today, 2024)
This article examines Black preaching as a vital force in African American communities, offering a powerful testament to resilience, spiritual enlightenment, and social transformation. Black preaching emerges as a beacon of hope and resistance amidst oppressive conditions, weaving together theological insight, cultural richness, and communal resilience. Through a rich historical lens, the article explores the performative and substantive dimensions of Black preaching, highlighting its capacity to navigate complex theological and social realities. While acknowledging moments of complicity and challenge within Black preaching, this article emphasizes its enduring legacy as a catalyst for liberation and justice. Ultimately, Black preaching emerges as a dynamic expression of faith, embodying the enduring struggle for dignity, justice, and freedom within the African American experience.